Privacy aware conceptual desgin of flooding message in vehicular Ad-Hoc network - Sayyadi, Hamed (2013)
A Vehicular Ad-Hoc Network (VANET) facilitates communication between vehicles and between vehicles and infrastructure. The study of VANETs has recently become an increasingly popular research topic in the area of wireless networking as well as the automotive industries. The goal of VANET research is to develop a vehicular communication system to enable quick and cost-efficient distribution of data for the benefit of passengers’ safety or comfort. Usually, security in routing has conflict with privacy. Although, all prior works improved security on VANET routing, there is no strong advancement on privacy. This study designed a new routing protocol based on both identity and position to improve privacy compliant secure routing in VANET. The new routing protocol called as PIDP contains five kinds of packets: Route Request, Route Reply, Source Route Reply, Data, and Acknowledgement. The first three packets are based on position and the rest packets are based on identity. As a result, PIDP can hide both position and real identity of terminal nodes from intermediate nodes.